Update Energy-Efficient Ethernet. - Patel-Predd, P. (IEEE spectrum)
Ethernet link speeds of 100 megabits per second or even 1 gigabit per second are typical right now in local area networks. Studies show that on average, people use their Ethernet links at full throttle less than 5 percent of the time. But the circuitry on the network-interface controller, the chip that connects computer to the network, is always running at full speed, wasting power. The network-interface controllers in the United States - computers, switches, and routers all have them burned through 5.3 terawatt-hours of energy, enough to keep 6 billion 100-watt lightbulbs shining all year. The savings would be even greater if the links were switching between 10 Gb/s and 100 Mb/s.